Mechanisms of inactivation of mismatch repair genes in human colorectal cancer cell lines: the predominant role of hMLH1. - Wheeler, J; Beck, N; Kim, H; Tomlinson, I; Mortensen, N; Bodmer, W (1999)
Fifteen to twenty-five percent of sporadic colorectal carcinomas are replication error (RER) positive. Because the frequency of mutations in the mismatch repair genes (hMLH1 and hMSH2) is low in these tumors, we have investigated the role of mutational inactivation, methylation of the promoter region, and loss of heterozygosity (LOH) as a possible explanation for the mutator phenotype of RER+ colorectal cancer cell lines. Genomic DNA was extracted from a panel of 49 human colorectal cancer cell lines. The RER status was determined by amplification of BAT-26. All exons of hMLH1 and hMSH2 were amplified with the PCR and screened by using single-strand conformational polymorphism and direct sequencing. The methylation status was ascertained by methylation-specific PCR after bisulfite modification of DNA. Western blotting for hMLH1 was performed on methylated cell lines before and after the addition of the demethylating agent 5-azacytidine. LOH was sought by GENESCAN analysis of amplified CA repeat markers and indirectly by determining the number of homozygotes in the cell lines and human random controls. Twelve cell lines from ten tumors (24%) were RER+. Hypermethylation of the hMLH1 promoter occurred in five of ten (50%) RER+ tumors, whereas three of thirty-two (6%) RER tumors showed partial methylation. None of the fully methylated cell lines expressed hMLH1, although all reexpressed hMLH1 after treatment with 5-azacytidine. There was no LOH in the RER+ tumors in either hMLH1 or hMSH2. Our results suggest that mutations of hMLH1 together with hypermethylation of the promoter region, but not LOH, are the cause of the mutator phenotype in the majority (70%) of RER+ tumors.